EFEKTIFITAS SENSORI INTEGRASI UNTUK MENINGKATKAN KEMAMPUAN MENULIS PERMULAAN PADA ANAK AUTIS DI TI-JI HOME SCHOOLING PADANG - Petrin - Kasdanel (Universitas Negeri Padang, 2013)
This research background by the problems that researchers find in Home Schooling Padang Tiji, an autistic child who was eight years old, still has not been able to write the beginning, especially the vowels (a, i, u, e, o). This research Single Subject Research approach, the ABA design and data analysis techniques using visual analysis chart. Measurement variables using the percentage of each vowel can be written children properly. Observations made with the first three sessions, the session before being given intervention baseline (A1) performed seven times of observation, the percentage of vowels writing skills in this condition lies in the range of 0%, and 20% is at the confluence of unity, kadua third, fifth, sixth and seventh day the child can not be any writing beginning in vowels, but at a meeting of the four children to write a single vowel is the letter